Analisis Manhaj al-Khas Kitab Tafsir At-Tahrir wa at-Tanwir karya Ibnu `Asyur - Ali, Muhammad Hasan; Edi Komarudin; Asep Ahmad Fathurrohman (Jurnal Penelitian Ilmu Ushuluddin, 2025)
Interpretation methods are generally divided into four types, namely tahlili, ijmali, muqaran, and maudhui. However, beyond these general methods, each interpreter, or mufasir, has their own unique perspective when interpreting the Quran, known as manhaj al-khash or the interpreter's special method. This research aims to discuss Ibn Ashur's manhaj al-khash in writing his exegesis, At-tahrir wa at-Tanwir. This study uses a qualitative research method based on literature review. The primary source in this research is Tafsir At-tahrir wa at-tanwir Juz 27, while the secondary sources refer to books, texts, and articles related to the research theme. The results of this study indicate that there are at least fifteen manhaj al-khash of Ibn Ashur in writing his exegesis, pertaining to the methods of using interpretation sources as well as the writing methods in his exegesis.